2018
DOI: 10.1001/jamanetworkopen.2018.1465
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Autism Spectrum Disorders With or Without Intellectual Disability and Depression in Young Adulthood

Abstract: Key Points Questions Are individuals with autism spectrum disorders more likely to have depression in adulthood than the general population, and do these risks have a familial basis and differ by coexisting intellectual disability? Findings In this Swedish population-based cohort study of 223 842 participants with a nested sibling comparison, individuals with autism spectrum disorders, especially those without intellectual disability, had a greater risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
6
49
0
2
Order By: Relevance
“…When comparing ADHD and ASD in our epidemiological data, we observed significant differences in the associations with all psychiatric comorbidities examined, with individual estimates being consistent with previous studies (11)(12)(13)15,24,(30)(31)(32). The most marked differences were found for SCZ and SUD, in which SCZ was more common in adults with ASD and SUD was more common in adults with ADHD.…”
Section: Different Comorbidities In Adults With Adhd and Asdsupporting
confidence: 89%
“…When comparing ADHD and ASD in our epidemiological data, we observed significant differences in the associations with all psychiatric comorbidities examined, with individual estimates being consistent with previous studies (11)(12)(13)15,24,(30)(31)(32). The most marked differences were found for SCZ and SUD, in which SCZ was more common in adults with ASD and SUD was more common in adults with ADHD.…”
Section: Different Comorbidities In Adults With Adhd and Asdsupporting
confidence: 89%
“…To our knowledge this is the first study of the difference in prevalence rates of anxiety disorders for adults with ASD with and without ID. The finding of higher rates of anxiety disorders amongst adults with ASD without ID compared with adults with ASD and ID is consistent with some of the results from studies of children with ASD and anxiety disorder (Weisbrot et al 2005;Sukhodolsky et al 2008;Mayes et al 2011) and with a recent study of depression in ASD (Rai et al 2018), and may be due to a number of factors. Increased rates of anxiety disorders may be present in individuals without ID due to increased cognitive awareness of their impairments (Bauminger et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that common mental disorders could be more prevalent in individuals with ASD without intellectual disability (ID), because they may have more insight into their problems. This pattern has been observed for depression (Rai et al 2018) and for OCD (Meier et al 2015) in higher functioning individuals with ASD. To date, studies of the prevalence of other anxiety disorders in adults with autism and ID have predominantly focussed on comparing individuals with intellectual disability with and without autism, with variable results regarding whether autism increases the rates of anxiety disorders, although these studies have been relatively small (Bakken et al 2010;Bradley and Bolton 2006;Charlot et al 2008;Gillott and Standen 2007).…”
Section: Electronic Supplementary Materialssupporting
confidence: 67%
“…Difficulties in sociability can therefore potentially be seen as a cross-disorder overlapping trait in these frequently co-occurring disorders (i.e. (Chisholm, Lin, Abu-Akel, & Wood, 2015;Lee & Lyketsos, 2003;Rai et al, 2018)) with potentially shared underlying mechanisms relating them. The withdrawal from friends, family, and colleagues, is one of the symptoms that is particularly burdensome for relatives of those affected by such disorders.…”
Section: Introductionmentioning
confidence: 99%